Effects of PAHs on meiofauna from three estuaries with different levels of urbanization in the South Atlantic - Renan B. da Silva; Giovanni A. P. Dos Santos; Ana Luiza L. de Farias; Débora A. A. França; Raianne Amorim Cavalcante; Eliete Zanardi-Lamardo; Jose Roberto Botelho de Souza; Andre M. Esteves (PeerJ, 2022)
Estuarine environments are suggested to be the final receivers of human pollution and are impacted by surrounding urbanization and compounds carried by the river waters that flow from the continent. Polycyclic aromatic hydrocarbons (PAHs) are among the contaminants that can reach estuaries and can directly affect marine conservation, being considered highly deleterious to organisms living in these environments. This research investigated the meiofauna of three estuaries exposed to different levels of urbanization and consequently different levels of PAH concentrations, in order to assess how these compounds and environmental factors affect the distribution, structure and diversity of these interstitial invertebrates. A total of 15 major meiofauna groups were identified, with Nematoda being the dominant taxon (74.64%), followed by Copepoda (9.55%) and Polychaeta (8.56%). It was possible to observe significant differences in all diversity indices studied in the estuaries. With the exception of average density, the diversity indices (richness, Shannon index and evenness) were higher in the reference estuary, Goiana estuarine system (GES). On the other hand, the Timbó estuarine system (TES) had the lowest Shannon index value and richness, while the Capibaribe estuarine system (CES) had the lowest evenness value. The latter two estuaries (TES and CES) presented intermediate and high levels of urbanization, respectively. The ecological quality assessment (EcoQ) in the studied estuaries was classified from Poor to Moderate and the estuary with the lowest demographic density in its surroundings, GES, showed a better ecological quality (Moderate EcoQ). A significant distance-based multivariate linear modelling regression (DistLM) was observed between the environmental variables and the density of the meiobenthic community, where PAHs and pH were the main contributors to organism variation. The sediments were characterized by predominance of very fine sand and silt-clay in the most polluted environments, while the control site environment (GES) was dominated by medium grains. The highest concentrations of PAHs were found in the most urbanized estuaries, and directly affected the structure of the interstitial benthic community. The metrics used in the present study proved to be adequate for assessing the environmental quality of the investigated estuaries.